Association Between Different Vericiguat Dose Exposures, Concomitant Quadruple Heart Failure Therapy, and Myocardial Fibrosis Burden in Older Adults with Worsening Heart Failure with Reduced Ejection Fraction - Liyong Ge; Guoqiu Wang; Anning Zeng; Wei Li (The Anatolian Journal of Cardiology, 2026)
Background: Older adults with worsening heart failure with reduced ejection fraction (HFrEF) remain high risk despite quadruple guideline-directed medical therapy (GDMT-4). Whether vericiguat exposure relates to change in myocardial fibrosis is unknown. Methods: A single-center, prospective cohort of patients ≥65 years with HFrEF [left ventricular ejection fraction (LVEF) ≤40%] after a recent worsening event (enrollment from January 2022 to December 2023 with 12-month follow-up) was conducted. Vericiguat exposure was modeled as time-updated, lagged dose across intervals. Baseline therapy was quantified with a GDMT-4 Index (0-7). Co-primary endpoints were 12-month change in cardiovascular magnetic resonance extracellular volume (ECV, %) and a serum fibrosis composite z-score. Extracellular volume used weighted models with observation weights. Multiplicity for co-primary endpoints was controlled by Holm–Bonferroni. Recurrent rehospitalizations used Andersen–Gill and marginal structural models. Results: Of 268 screened, 210 enrolled and 198 formed the analysis set. Paired ECV was available for 146 (73.7%). High vs. low exposure was associated with greater ECV reduction (−1.3 percentage points; 95% CI −2.1 to −0.5; Holm-adjusted P = .002) and serum composite improvement (−0.23 SD; 95% CI −0.37 to −0.09; Holm-adjusted P = .004). Secondary endpoints favored higher exposure (global longitudinal strain +1.1%, N-terminal pro-B-type natriuretic peptide geometric mean ratio 0.84, 12-item Kansas City Cardiomyopathy Questionnaire +6.1; q ≤ 0.045). The exposure × GDMT-4 interaction for ΔECV (P = .031) showed larger benefit at higher GDMT-4. Over 195 person-years, 52 rehospitalizations occurred; high exposure was associated with fewer events (Hazard ratio 0.74, 95% CI 0.53–1.03; exploratory). Safety events were infrequent and balanced. Conclusions: Greater time-updated vericiguat exposure was linked to less fibrosis and an exploratory reduction in rehospitalizations, especially with higher GDMT-4.